1999
DOI: 10.1073/pnas.96.5.2301
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase gene disruption conferred mice resistant to streptozotocin-induced diabetes

Abstract: Streptozotocin (STZ), a glucose analogue known to induce diabetes in experimental animals, causes DNA strand breaks and subsequent activation of poly(ADPribose) polymerase (Parp). Because Parp uses NAD as a substrate, extensive DNA damage will result in reduction of cellular NAD level. In fact, STZ induces NAD depletion and cell death in isolated pancreatic islets in vitro. Activation of Parp therefore is thought to play an important role in STZ-induced diabetes. In the present study, we established Parp-defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
194
1
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(205 citation statements)
references
References 26 publications
6
194
1
4
Order By: Relevance
“…Whereas PARP-1 activation and subsequent NAD + depletion have been implicated as a major mechanism of HDS-induced pancreatic beta-cell destruction [27,28,29], we did not detect any linkage of NOD HDSsusceptiblity to the D1Mit36 (92.3 cM) and D1Mit407 (101.5 cM) markers surrounding the corresponding gene at 98.6 cM in chromosome 1. This result is not really surprising since our previous studies showed that, in the NOD mouse, PARP-1 activation was not required for HDS-induced diabetes [6].…”
Section: Discussioncontrasting
confidence: 91%
“…Whereas PARP-1 activation and subsequent NAD + depletion have been implicated as a major mechanism of HDS-induced pancreatic beta-cell destruction [27,28,29], we did not detect any linkage of NOD HDSsusceptiblity to the D1Mit36 (92.3 cM) and D1Mit407 (101.5 cM) markers surrounding the corresponding gene at 98.6 cM in chromosome 1. This result is not really surprising since our previous studies showed that, in the NOD mouse, PARP-1 activation was not required for HDS-induced diabetes [6].…”
Section: Discussioncontrasting
confidence: 91%
“…Also, mice deficient in PARP are resistant to beta cell death mediated by streptozotocin, in spite of DNA fragmentation. The absence of PARP prevents the depletion of the cofactor NAD + and the subsequent loss of ATP [84,[88][89][90] and thus cell death.…”
Section: Beta Cell Toxicity Of Streptozotocinmentioning
confidence: 99%
“…The whole cell extracts or nuclear extracts were prepared [34] and then the proteins were fractionated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The proteins were electrotransferred into Immobilon-P (Millipore Co, Bedford, MA, USA).…”
Section: Immunoblottingmentioning
confidence: 99%
“…Damage to DNA by STZ (due to the DNA alkylating activity of its methyl nitrosourea moiety [30]) depletes NAD+, which in turn inhibits insulin biosynthesis and secretion and leads to beta cell death through energy depletion [32]. This conclusion is further supported by the observations that the mice deficient in poly (ADP-ribose) polymerase (PARP) are resistant to STZ-mediated beta-cell death [33][34][35].…”
Section: Introductionmentioning
confidence: 99%